“I need help”: a study of spiritual distress among people diagnosed with bipolar disorder in Malaysia - Mohamad Shariff, Nurasikin; Wright, Nicola; Crawford, Paul (Malaysian Journal of Medicine and Health Sciences, Faculty of Medicine and Health Sciences, 2021)
Little is known about spiritual distress in people with bipolar disorder, where they are inclined to maladaptive coping. Given the contextual influence of religion on Malaysians, this study is aimed to explore the phenomenon of spiritual despair and recovery, as experienced by a group of people with bipolar disorder. A qualitative one-to-one interview was conducted on 25 participants of multi-religious background and diagnosed with bipolar disorder recruited from two psychiatric clinics in Kuala Lumpur, Malaysia. All interviews were audiotaped and transcribed verbatim. The interview data were analysed using a thematic analysis approach. This paper presents the theme of ‘Restoring hope, meaning, and purpose’ with three subthemes; 1) experiencing spiritual despair, 2) engaging in spiritual meaning-making, and 3) orienting the spiritual life. The finding captured the participants’ experience of having despair in God over the ‘fated experience’ (takdir), and they abandoned religious practice during the period. However, participant narratives also indicate the possibility that their spiritual despair can be mitigated, endured, or transformed through the support of family members. The participants also highly recommended that spirituality may be combined with medical interventions, such as medication prescribed by their psychiatrist. This study highlights the importance of supportive family in advancing towards religious-spiritual pathways and the advantages of medical interventions in controlling bipolar symptoms during their spiritual despair. This study favours extending the role of mental health service in providing sessions for the users to voice out their spiritual concerns.